The effect of preoperative consumption of potatoes on succinylcholine-induced block and recovery from anesthesia - Bestas, Azize; Goksu, Hulya; Erhan, Omer Lutfi (Springer Heidelberg, 2013)
Potatoes contain solanaceous glycoalkaloids (SGAs), which inhibit both butyrylcholinesterase (BuChE) and acetylcholinesterase (AChE). The present study investigated the effect of preoperative consumption of potatoes on succinylcholine-induced block and recovery from anesthesia. ASA I-II, adult patients, scheduled for elective surgery, were included in a randomized, blind and controlled study. Patients were randomly divided into two groups. Patients in Group P (n = 21) ate a standard portion of potatoes in their last meal prior to pre-operative fasting, while patients in Group C (n = 23) ate food not containing SGAs. Patients were premedicated with midazolam. Anesthesia was induced with thiopental and fentanyl, and maintained with sevoflurane in 50 % O-2/air and fentanyl, as needed. Succinylcholine 1 mg kg(-1) was administered to facilitate endotracheal intubation. Duration of succinylcholine blockade, awakening and recovery times from anesthesia were measured. Serum BuChE levels were also measured at baseline and 4 time-points within 24 h post-consumption. Duration of succinylcholine-induced neuromuscular block, awakening and recovery time from anesthesia was significantly longer in Group P than in Group C (p < 0.05). Serum BuChE levels decreased at 6 h after consumption start in Group P. In addition, in both groups, BuChE levels markedly decreased after succinylcholine blockade, increased thereafter, but did not return to baseline within 24 h of consumption start. None of these differences observed in BuChE levels was statistically significant. This study suggests that potatoes eaten before anesthesia can prolong the duration of succinylcholine-induced neuromuscular block and delay recovery from anesthesia.
Keywords: Anesthesia; Succinylcholine; Potatoes; Solanaceous glycoalkaloids